IMPLEMENTASI ASAS KEBEBASAN BERKONTRAK DALAM AKAD PEMBIAYAAN MUDHARABAH YANG DILAKSANAKAN OLEH KOPERASI SYARIAH KAUM IBU AL-IKHLAS SUKADONO, TANJUNG GUSTA, DELI SERDANG - NAZMA HUSNA (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1. H. Zamahksyari Bin Hasballah Thaib, LC, MA, PhD2. Dr. Utary Maharani barus, SH, MHum3. Dr. Yefrizawati, SH, MHum The principle of freedom to make contracts or what is called Al-Hurriyah in Islamic Laws which means that all concerned parties are free to make contracts, to decide with whom and the object of the contract, and to determine how to make settlement in the future as long as it is not contrary to Islamic Sharia Laws. Mudarabah (sharing the profit and loss with venture capital) financing contract is a contract between shahibul maal (financer) who provides 100% of capital to mudarib (working partner) for a productive business. The mudarabah financing contract done by the sharia cooperative is unilaterally determined as shahibul maal. The research problems are how mudarabah financing contract is regulated based on Islamic Laws, how the principle of freedom to make contracts is implemented in form of a standard contract in the Sharia Cooperative of the Al Ikhlas Motherhood in Sukadono in accordance with Islamic Laws, and how about the legal protection for the members involved in the contract.This is a normative and empirical juridical research which is analytically descriptive. It uses primary data collected from interviews and questionnaires, and secondary data collected from primary, secondary, and tertiary legal materials. This research is done in Sharia Cooperative of the Al Ikhlas Motherhood in Sukadono, Jalan Tanjungn Permai No. 303, Deli Serdang. The analysis used is qualitative data analysis.Mudarabah financing contract is regulated in a verse of the Quran i.e. Surah Al- Muzzammil verse 20, Hadith in Ibnu Majah No. 2280, Ijma’, a number of Sahabah handed to a mudarib the property of orphand as mudarabah, Fatwa DSN-MUI No. 07/DSN-MUI/IV/2000 on Mudarabah Financing (Qiradh), stating that mudarabah financing contract is an agreement between shahibul maal who gives100% of capital to mudarib for a productive business. The principle of freedom to make contracts in the mudarabah financing contract in form of a standard contract according to Islamic Laws that is done by the Sharia Cooperative of the Al Ikhlas Motherhood in Sukadono is not implemented, because in spite of the members’ willingness, the standard contract is contrary to Islamic Laws. The legal protection for the members involved in the mudarabah financing contract done by the Sharia Cooperative of the Al Ikhlas Motherhood in Sukadono, Tanjung Gusta, is the khiyar i.e. khiyar asy-syart, meaning that when there is a dispute and it cannot be settled by a discussion, it can be settled by the Religious Court.Keywords: Al-Hurriyah, Sharia Cooperative, Mudarabah Contract